The Origin Recognition Complex: From Origin Selection to Replication Licensing in Yeast and Humans - Bik-Kwoon Tye; Yuanliang Zhai (Biology, 2023)
Understanding human DNA replication through the study of yeast has been an extremely fruitful journey. The minichromosome maintenance (MCM) 2–7 genes that encode the catalytic core of the eukaryotic replisome were initially identified through forward yeast genetics. The origin recognition complexes (ORC) that load the MCM hexamers at replication origins were purified from yeast extracts. We have reached an age where high-resolution cryoEM structures of yeast and human replication complexes can be compared side-by-side. Their similarities and differences are converging as alternative strategies that may deviate in detail but are shared by both species.